Józef Jakubowski (1899–1984) – activist in scout, community, and émigré organisations in the light of Polish and French archival resources - Anna Pachowicz (Folia Historica Cracoviensia)
The main purpose of this paper is to provide an insight into the life, activities, and preserved archival documents concerning Józef Jakubowski (1899–1984), whose work in support of Polish emigrants residing in France during the Second World War deserves highest recognition and respect. Jakubowski was born in Warsaw, where he spent his childhood, completed primary and secondary education, and began his studies at the Warsaw University of Technology in 1917. He was was actively involved in the scouting movement. His participation in the Polish–Soviet War forced him to leave the university . It was only in 1924 that he completed his higher education at another university, the Higher School of Commerce. His professional life also started in Warsaw, where he worked for the Association of Polish Merchants until 1939. His life was interrupted by the Second World War, and he decided to emigrate first to Switzerland and then to France. At that time of his life, he became involved with the Polish Red Cross. He was primarily involved in developing forms of aid and organising support for Poles in France. Once the Polish Red Cross was banned from further activities, he worked in the Welfare Society for the Poles in France. He cooperated with the Polish Resistance Movement in France and with military authorities on the evacuation of the Polish armed forces to England, as well as with many institutions, including the French Red Cross, the Department of Social Welfare for Foreigners, the International Refugee Organisation, and the Association of Polish Veterans. The archival documents concerning Jakubowski, surviving at the Central Archives of Modern Records in Warsaw and at the Polish Library in Paris, make it possible to reconstruct not only the facts of his life but also the events related to the functioning of the institutions, organisations, and associations he worked for.